PENGARUH HARGA DAN CITA RASA TERHADAP KEPUASAN KONSUMEN (Studi Kasus ‘’Rumah Makan Ayam Bakar Pinggir Jalan’’ Pondok Kelapa) - Muhammad Ridwan; S Sunarno; Ulumil Huda (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This study aims to determine the ''Effect of Price and Taste on Consumer Satisfaction at'' Pondok Kelapa Street Grilled Chicken Restaurant. The sample used was 100 respondents. This research uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test. The analysis in this study uses multiple regression analysis, multiple correlation analysis, coefficient of determination and hypothesis testing. The results of this t-test study indicate that the price variable (X1) has a positive and significant effect on consumer satisfaction (Y) with a tcount of 4.696 > ttable of 1.661 and a significant value of 0.000 <0.05, the Taste variable (X2) has a positive and significant effect on Consumer Satisfaction (Y) with a tcount of 3.988 > ttable of 1.661 and a significant value of 0.000 <0.05. The correlation value of 0.702 means that it shows a strong and positive relationship. The coefficient of determination is 0.493. This means that the influence of price (X1) and taste (X2) on consumer satisfaction (Y) is 49.3% and the remaining 50.7% is influenced by other factors outside this study.